Water-adaptive and repeatable self-healing polymers bearing bulky urea bonds. Issue 1 (9th November 2017) - Park, J. I.; Choe, A.; Kim, M. P.; Ko, H.; Lee, T. H.; Noh, S. M.; Kim, J. C.; Cheong, I. W.
Abstract : A crosslinked copolymer having a reversible covalent bond between a bulky amine and an isocyanate presents reshapable, repeatable, and water-adaptive self-healing properties. Abstract : Self-healing polymers bearing reversible and bulky urea bonds were prepared by free-radical copolymerization followed by crosslinking with diisocyanates. Linear prepolymers (PtB) were first synthesized from 2-( tert -butylamino)ethyl methacrylate ( t BAEMA), methyl methacrylate (MMA), and n -butyl acrylate (BA), in a molar ratio of 1 : 10 : 10, and then crosslinked with 1, 6-diisocyanatohexane (HDI) or isophorone diisocyanate (IPDI) to fabricate self-healing polymers. The reversible bonding–debonding between the t BAEMA of the polymer backbone and the isocyanate units of the crosslinker in the self-healing polymer facilitates rapid, repeatable, and water-adaptive self-healing performance, which has been extensively investigated using 1 H-NMR, DSC, FT-IR, AFM, optical microscopy, and rheometric analyses. Percentage recovery (% R ) and self-healing efficiency (%SHE) were also studied using tensile and single-scratch tests, respectively, and compared with a control sample. It was revealed through extensive analyses that self-healing against a single scratch can be accelerated and repeated up to a certain number of times even in water, although the self-healing polymers are not water-resistant. We also demonstrated that a self-healable tube capable of containing flowing water could be fabricated from a self-healing polymer sheet by using reversible bonding–debonding characteristics of a reversible bulky urea bond.